Degradation of sulfanomides in water using direct UV photolysis and UV/PS processes - Peh, Anthony Young Siang (2017)
The presence of residual antibiotics in water has sparked an increased social concern, where it is classified as a rapidly growing class of contaminants. The adverse effects have been associated with its rising incidence of antibiotic-resistant genes and bacteria. In particular sulfonamides (SAs) have been a commonly used antibiotic for treating human diseases and as veterinary medicine. Fifteen SAs were chosen as target pollutants in this project. Their photodegradation rates were investigated using a low-pressure UV-254 Hg lamp by direct UV photolysis and UV/persulfate (UV/PS) processes. Removal of SAs under direct UV photolysis processes is inefficient due to their low quantum yield, while the photodegradation of SAs significantly increases with the addition of persulfate in the UV/PS system due to the generation of sulfate radicals. A ratio of 20:1 [oxidant/pollutant] was applied in this study. As compared to the maximum removal of 50% by direct UV photolysis for up to an hour, UV/PS system demonstrates a maximum removal efficiency of 98% for merely 7 minutes. A comparison was made between UV/PS and UV/H2O2 processes with the same oxidant to pollutant ratio. The determined second-order rate constants of radicals with SAs show that UV/PS is more efficient than UV/H2O2 in degrading SAs. Quantitative structure activity relationship (QSAR) model was then developed using twelve quantum-chemical descriptors to correlate the photodegradation rate and the structural characteristics of SAs. Due to the larger independent variables of Fukui indices and qH+, they are considered as the key parameters in the optimal model for direct UV photolysis. QSAR model was also developed with the first-order rate constant by UV/PS process. Fukui indices, Ehomo and Elumo are considered as the key parameters in the regression model due to a higher independent variable.